Japan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1996)
This Selected Issues paper analyzes Japan's medium- and long-term fiscal challenges. It discusses the initiatives that will be necessary to cope with Japan's medium- and long-term fiscal challenges. It describes medium- and long-term projections of the fiscal position, and assesses the size of the consolidation measures needed to restore long-term fiscal sustainability. The paper explores possible options for consolidation and offers a representative package of such measures. The paper also describes the projected baseline path for the long-term fiscal balance, incorporating the long-term pension reform plan formulated in 1994.